2020
DOI: 10.3389/fcell.2020.00807
|View full text |Cite
|
Sign up to set email alerts
|

The Pathogenic Effects of Fusobacterium nucleatum on the Proliferation, Osteogenic Differentiation, and Transcriptome of Osteoblasts

Abstract: As one of the most common oral diseases, periodontitis is closely correlated with tooth loss in middle-aged and elderly people. Fusobacterium nucleatum ( F. nucleatum ) contributes to periodontitis, but the evidence in alveolar bone loss is still unclear. In this study, cytological experiments and transcriptome analyses were performed to characterize the biological process abnormalities and the molecular changes of F. nucleatum -stimulated os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…So far, little is known about the role of BIRC3 in oral physiology and pathophysiology. BIRC3 was recently identified as one of many other regulated genes in F. nucleatum -stimulated rat osteoblasts by whole-transcriptome analyses [ 14 ]. Moreover, periodontal ligament (PDL) cells have been shown to produce BIRC3, which could be increased by high tensile forces [ 15 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, little is known about the role of BIRC3 in oral physiology and pathophysiology. BIRC3 was recently identified as one of many other regulated genes in F. nucleatum -stimulated rat osteoblasts by whole-transcriptome analyses [ 14 ]. Moreover, periodontal ligament (PDL) cells have been shown to produce BIRC3, which could be increased by high tensile forces [ 15 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The superoxide dismutase 2 (SOD2) and baculoviral IAP repeat-containing protein 3 (BIRC3), also known as cIAP2, are two molecules that seem to be involved in the actions of microbial and mechanical signals on periodontal cells and tissues [ 12 , 13 , 14 , 15 ]. SOD2 can convert toxic superoxide into hydrogen peroxide and diatomic oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that absorption of the alveolar bone by Porphyromonas gingivalis, Campylobacter rectus, and Fusobacterium nucleatum is mediated by arachidonic acid metabolites, such as prostaglandins (Gao et al, 2020). Fusobacterium nucleatum can act on osteoblasts, which is reflected in the reduced expression of osteogenic genes and proteins (Reis et al, 2016), inhibition of cell differentiation, formation of mineralized nodules, and increased production of pro-inflammatory factors (Gao et al, 2020) (Figure 1).…”
Section: Fusobacterium Nucleatummentioning
confidence: 94%
“…Amyloid-like FadA was shown to induce periodontal bone loss and promote colorectal cancer (CRC) progression in mice ( Meng et al, 2021 ). Other research teams also found that F. nucleatum could inhibit cell proliferation, promote cell apoptosis, and elevate pro-inflammatory cytokine production of osteoblasts or Gingiva-Derived Mesenchymal Stem Cells ( Kang et al, 2019a ; Gao et al, 2020 ). More experiments are needed to support this conclusion in the future.…”
Section: Discussionmentioning
confidence: 98%